1998
DOI: 10.1108/02656719810204892
|View full text |Cite
|
Sign up to set email alerts
|

On the gap between theory and practice of process capability studies

Abstract: Historically, a theoretical framework has been established to judge whether a process is capable or not. These studies, called process capability studies, have received both positive and negative comments. Both researchers and practitioners have indicated that the concept of process capability studies is often misused in practice. This article aims to identify and quantify this misuse, and when it is severe, try to provide some explanations of its origin. The survey presented is primarily based on questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…If a process is out of control, it has historically failed to display a reasonable degree of consistency and it is illogical to expect that it will spontaneously do so in the future. Therefore, a capability study monitoring an unstable process will only express the capability of the process at that very moment and nothing can be said about the capability of the process in the future (Deleryd, 1998). We know that the best tool to check whether or not the process is in statistical control is control charts.…”
Section: Introductionmentioning
confidence: 99%
“…If a process is out of control, it has historically failed to display a reasonable degree of consistency and it is illogical to expect that it will spontaneously do so in the future. Therefore, a capability study monitoring an unstable process will only express the capability of the process at that very moment and nothing can be said about the capability of the process in the future (Deleryd, 1998). We know that the best tool to check whether or not the process is in statistical control is control charts.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that only data collected from a stable process can provide a true picture of its capability. Non-random patterns on a control chart suggest the presence of assignable-cause variations that will make the result of any capability index meaningless (Deleryd 1998). For processes with unknown trend patterns, traditional process capability indices should not be used.…”
Section: Introductionmentioning
confidence: 99%
“…They reduce the dimension of the multivariate QCs using the covariance distance (CD). Many studies in the literature consider non-normal PCIs [8,11,[42][43][44][45][46][47][48][49][50]. Additionally, a few studies focus on multivariate non-normal process capabilities.…”
Section: Introductionmentioning
confidence: 99%